2021
DOI: 10.3390/pharmaceutics13040546
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Solubility, Dissolution, and Bioavailability of Metronidazole via Cocrystallization with Ethyl Gallate

Abstract: Metronidazole (MTZ) is an antibacterial drug widely used for the treatment of protozoan and anaerobic infections in humans and animals. However, its low bioavailability necessitates the frequent administration of a high dose to attain an effective plasma concentration profile for therapy. To reduce the dose of MTZ, we have prepared a new cocrystal between MTZ and ethyl gallate (EG). The solid-state properties of MTZ-EG were characterized using complimentary techniques, including thermal, spectroscopic, microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…During the past 20 years, cocrystallization has proved to be an effective approach to tailor physicochemical properties of active pharmaceutical ingredients (APIs) through reliable supramolecular synthons based on various hydrogen-bonding interactions. Solubility, dissolution, and bioavailability of APIs could be greatly enhanced by the formation of cocrystals. Moreover, pharmaceutical cocrystals could be endowed with superior humidity, thermal and photo stability. Recently, some pharmaceutical cocrystals showing potential extended release properties have been prepared, which indicated that cocrystallization could be a new strategy for achieving extended release of APIs. Like single APIs, however, polymorphism in pharmaceutical cocrystals is also quite common and the polymorphs of cocrystals can display significantly different properties. Therefore, polymorphism is an important consideration in the development of pharmaceutical cocrystals. In view of the fact that a high proportion of drugs are available in racemic form, the preparation of cocrystal polymorphs based on racemic APIs should be an important topic.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 20 years, cocrystallization has proved to be an effective approach to tailor physicochemical properties of active pharmaceutical ingredients (APIs) through reliable supramolecular synthons based on various hydrogen-bonding interactions. Solubility, dissolution, and bioavailability of APIs could be greatly enhanced by the formation of cocrystals. Moreover, pharmaceutical cocrystals could be endowed with superior humidity, thermal and photo stability. Recently, some pharmaceutical cocrystals showing potential extended release properties have been prepared, which indicated that cocrystallization could be a new strategy for achieving extended release of APIs. Like single APIs, however, polymorphism in pharmaceutical cocrystals is also quite common and the polymorphs of cocrystals can display significantly different properties. Therefore, polymorphism is an important consideration in the development of pharmaceutical cocrystals. In view of the fact that a high proportion of drugs are available in racemic form, the preparation of cocrystal polymorphs based on racemic APIs should be an important topic.…”
Section: Introductionmentioning
confidence: 99%
“…Metronidazole (MTZ) is an effective antiprotozoal and antibiotic medicine, which is on the list of essential medicines worldwide [31]. It is used for the treatment of infections caused by anaerobic bacteria and various protozoan infections including giardiasis and trichomoniasis.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of supramolecular synthon or hydrogen-bonded building units was later developed by Desiraju . Cocrystal formation has become a powerful tool for enhancing key pharmaceutical properties, including stability, dissolution, , bioavailability, and manufacturability in the industry. Other applications, such as taste masking and toxicity reduction, have also been reported.…”
Section: Introductionmentioning
confidence: 99%